PRESUMED FOVEAL BACILLARY LAYER DETACHMENT IN A PATIENT WITH TOXOPLASMOSIS CHORIORETINITIS AND PACHYCHOROID DISEASE. Issue Volume 15:Issues 4(2021) (July 2021) - Mehta, Nitish; Chong, Jillian; Tsui, Edmund; Duncan, Jacque L.; Curcio, Christine A.; Freund, K. Bailey; Modi, Yasha
Abstract : Purpose: To report a detachment that apparently separated photoreceptor inner segment myoids from inner segment ellipsoids as a manifestation of toxoplasmosis chorioretinitis in a patient with pachychoroid spectrum disease. Methods: Multimodal imaging including fundus photography, spectral domain and enhanced-depth imaging optical coherence tomography (OCT), indocyanine green angiography, and OCT angiography. Results: A 33-year-old man with a history of toxoplasmosis chorioretinitis reported 1 week of decreased vision to 20/200 in his right eye. Examination of the right eye demonstrated mild vitritis with recurrent chorioretinitis inferior to the fovea and adjacent to a chorioretinal scar. A dome-shaped, foveal photoreceptor layer-splitting detachment was noted on OCT. Because degenerating cone photoreceptors are capable of shedding their inner segments, we inferred the location of the detachment at the level of the inner segment myoid and provided a histological example of such from an unrelated donor case. In addition, multimodal imaging revealed dilated choroidal veins (pachyvessels) with attenuation of the inner choroid in both eyes and asymptomatic findings of central serous chorioretinopathy in the left eye. After 1 month of antibiotic and steroid therapy, the chorioretinitis resolved, as did the detachment. Hyperreflective foci on the vitreoretinal interface were appreciated with en face OCT that appeared to aggregate throughout the course of therapy, induce inner retinal striae, and resolve without inducing epiretinal membrane formation. Conclusion: Patients with preexisting pachychoroid spectrum disease may manifest a more significant retinal fluid accumulation in the setting of superimposed chorioretinal inflammation. In this case of macular toxoplasmosis chorioretinitis, inflammation manifested as a retinal detachment at the level of photoreceptor inner segment myoids that we named as a bacillary layer detachment. In this case, inflammatory sequelae of toxoplasmosis reactivation responded well to oral and intravitreal therapy. Abstract : A 33-year-old man was found to have a photoreceptor splitting detachment herein described as a bacillary detachment secondary to macular toxoplasmosis that may have been exacerbated by underlying pachychoroid disease.